IMPLEMENTASI DESAIN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MTS.MATHLA’UL ANWAR PUSAT MENES PANDEGLANG - Nurul Wasi'ah; Siti Nurafifah; Imel Dayanti; Mumu Zainal Mutaqin (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2023)
This study aims to dig deeper into the structured PAI learning design which includes human elements, materials, media, equipment and procedures that influence each other to achieve learning objectives. These components are teachers, subject matter and students. The interaction between the three main components involves facilities and infrastructure, such as methods, media and the arrangement of the learning environment, so as to create a learning situation that enables the achievement of pre-planned goals. his research is located at MTS Mathlaul Anwar Menes Pandeglang Center. This type of research used qualitative research with a descriptive approach. Data collection techniques in this study were carried out through interviews, observation documentation. PAI learning designs relate to each other, namely students, learning objectives, learning methods, and learning evaluation. So that the learning process can be successfully carried out according to predetermined standards. In addition, the implementation of PAI learning plans is realized in the form of lesson plans that can be made with annual, semester, daily programs which are called learning unit programs. The preparation of the Annual Program is a general program for each subject to be developed by the subject teacher concerned